Pengembangan sumber belajar IPS melalui pemanfaatan lingkungan dalam meningkatkan keterampilan proses di Sekolah Dasar - Wurdjinem Wurdjinem (LPMPP Universitas Negeri Yogyakarta, 2006)
This article is about a research whose objectives are (1) to identify the factors causing teachers not to use the environment as a learning resource, (2) to discover the learning prosess of social sciences by developing environmental learning resources, (3) to discover the learning pattern in learning social sciences at elemntary school by developing environment learning resources, (4) to increase the process skill in learning social science, (5) to discover to class model of environmental advantages as a learning resource of social sciences, and (6) to increase student learning outcame in learning social sciences.This research used an approach employing an actian research conducted by PGSD lecturers collaboratively and elementary school teachers as partners. The calss action design employed spiraling cycles.